Explaining people's perceptions of invasive alien species: A conceptual framework - Shackleton, Ross T; Richardson, David M; Shackleton, Charlie M; Bennett, Brett; Crowley, Sarah L; Dehnen-Schmutz, Katharina; Estévez, Rodrigo A; Fischer, Anke; Kueffer, Christoph; Kull, Christian A; Marchante, Elizabete; Novoa, Ana; et al. (Journal of environmental management, 2019)
Human perceptions of nature and the environment are increasingly being recognised as important for environmental management and conservation. Understanding people's perceptions is crucial for understanding behaviour and developing effective management strategies to maintain, preserve and improve biodiversity, ecosystem services and human well-being. As an interdisciplinary team, we produced a synthesis of the key factors that influence people's perceptions of invasive alien species, and ordered them in a conceptual framework. In a context of considerable complexity and variation across time and space, we identified six broad-scale dimensions: (1) attributes of the individual perceiving the invasive alien species; (2) characteristics of the invasive alien species itself; (3) effects of the invasion (including negative and positive impacts, i.e. benefits and costs); (4) socio-cultural context; (5) landscape context; and (6) institutional and policy context. A number of underlying and facilitating aspects for each of these six overarching dimensions are also identified and discussed. Synthesising and understanding the main factors that influence people's perceptions is useful to guide future research, to facilitate dialogue and negotiation between actors, and to aid management and policy formulation and governance of invasive alien species. This can help to circumvent and mitigate conflicts, support prioritisation plans, improve stakeholder engagement platforms, and implement control measures.
Keywords: Stakeholder; Perception; Biological invasions; ekosystém; zavlečené druhy; Social; percepce; lidé; Attitudes; Synthesis; Beliefs; Ecosystem; Knowledge; Humans; Introduced Species; Conceptual model